Avaliação de Desempenho em Bioinformática: Estudo de caso de sistemas computacionais para a investigação de microRNAs - Aguiar, Rosana; Ambrosio, Leandro; Sepúlveda-Hermosilla, Gonzalo; Maracaja-Coutinho, Vinicius; Paschoal, Alexandre (Proceedings of the Workshop on Performance of Computer and Communication Systems (WPerformance), 2015)
This paper describe in details the computational evaluation of the miRQuest ( http://mirquest.integrativebioinformatics.me/ ) system which is a webserver and middleware architecture integrating different standardized softwares for microRNA (miRNA) investigation.